Flagellin-PAc Fusion Protein Inhibits Progression of Established Caries. (July 2015) - Bao, R.; Yang, J.Y.; Sun, Y.; Zhou, D.H.; Yang, Y.; Li, Y.M.; Cao, Y.; Xiao, Y.; Li, W.; Yu, J.; Zhao, B.L.; Zhong, M.H.; et al.
Dental caries remains one of the most common infectious diseases of humankind, which develops slowly throughout life, affecting children, adolescents, and adults. A vaccine against caries is urgently needed. We previously developed recombinant flagellin as a mucosal adjuvant for anti– Streptococcus mutans vaccines by nasal immunization. Furthermore, we demonstrated a fusion protein strategy that combined flagellin and the target surface adhesion protein (PAc) in a single construct. This construct enhanced specific IgA responses in oral fluids and provided improved prophylactic protection against caries. In the present study, we observed prolonged progression of dental caries in rats after S. mutans Ingbritt challenge. In addition, we observed a therapeutic effect of the flagellin-PAc fusion protein (KF-rPAc) against dental caries as a mucosal vaccine with a new immunization protocol. The present study demonstrated that KF-rPAc by nasal immunization can promote PAc-specific systemic and mucosal antibody responses and inhibit dental caries progression efficiently after the implant of S. mutans into the oral cavity of the rats. The rats immunized with KF-rPAc exhibited 53.9% caries reduction compared with the sham-immunized rats. Our data support the concept of administration of KF-rPAc to humans after infection and even caries that has begun to alleviate caries progression. In conclusion, our study demonstrated that KF-rPAc could be used as an anticaries therapeutic mucosal vaccine.